Fluid Inclusion Studies of Barite Disseminated in Hydrothermal Sediments of the Mohns Ridge - Marina D. Kravchishina; Vsevolod Yu. Prokofiev; Olga M. Dara; Boris V. Baranov; Alexey A. Klyuvitkin; Karina S. Iakimova; Vladislav Yu. Kalgin; Alla Yu. Lein (Minerals, 2023)
This article discusses the results of a fluid inclusion studies in barite collected at the Jan Mayen vent field area (Troll Wall and Perle and Bruse) and Loki’s Castle vent field on the Mohns Ridge segment of the Arctic Mid-Ocean Ridge. Three mafic-hosted volcanogenic massive sulfide deposits were examined within the active vent fields that adequately correspond to the geological settings of ultraslow-spreading ridges and P–T conditions. Hydrothermal sediments were investigated to determine the temperature and salinity of the fluids responsible for barite precipitation. The hydrothermal origin of the barite was confirmed by its morphology. Fluid inclusions are two-phase and homogenize into the liquid phase on heating at temperatures below 287 °C. The salt concentration in fluids trapped in inclusions is 2.6–4.4 wt.% NaCl eq. The crystallization temperatures varied from 276 °C to 119 °C and from 307 °C to 223 °C for the Jan Mayen and Loki’s Castle vent fields, respectively. The data obtained allowed us to confirm evidence of fluid phase separation in the hydrothermal systems and to expand our knowledge of the temperature and salinity of mineral fluids previously known from recent direct measurements during the cruises within the G.O. Sars research vessel. The fluid inclusions data obtained from barites emphasize the fluid features characteristic of volcanogenic massive sulfide deposits, the similarities and differences among the studied hydrothermal sites and allow comparisons with similar products from other active hydrothermal systems.